An empirical investigation on the impact of supply chain on business performance - Komala Martheraveeran (School of Business Innovation and Technopreneurship, University Malaysia Perlis, 2012)
Effective supply chains provide opportunities to create sustainable competitive advantage and enhance the competitive position of companies . This study was conducted to determine the impact of supply chain on business operations at Tesco in Selangor. The objective of this study is how supplier relationship, Customer relationship, Operations efficiency and Quality practices and Business Performance influence the business operations through the supply chain. There were a total of 110 respondents to this study from Tesco Kuala Selangor Tesco Rawang and Tesco Klang.